Sala Situacional Municipal - Hybrid monitoring and surveillance system for climate-related acute food insecurity in the Dry Corridor of Guatemala - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
The innovation has been co-designed with partners, the main government partner (Secretary for Food and Nutirition Security) is using the tool in several municipalities in the Dry Corridor, other NGO partners support the implementation of the tool in other municipalities of the rest of the country.